The Principle of Justice in the Weakness of Objective Rights Holders Against Privileges Rights Holders - Trisadini Prasastinah Usanti; Indira Retno Aryatie; Oemar Moechthar (Universitas Airlangga, 2023)
AbstractMaterial guarantees create material rights with superior characteristics. One is absolute, that is, the right holder can enforce material rights against anyone. It is as if nothing can beat the holder’s position of material guarantee in the event of a conflict with concurrent creditors and creditors holding privileges. However, this absolute character can be weakened by law. In certain circumstances, such as the right to collect the cost of saving the collateral object, the position of the creditor holding the material guarantee must surrender to the creditor with the privilege. Creditors can even threaten their position by not getting full repayment because the object of the material guarantee is to pay the bill from the creditor who holds the privilege first. The problem analyzed in this article concerns the principle of justice associated with weakening the characteristics of material rights in material guarantees for privileges. This study uses statutory, conceptual, and case approaches. The result of this study is that the creditor’s bills of the holder of the privilege arising from the salvage of collateral objects must take precedence over the bills of creditors of property security holders. This is considered fair, whereby the salvage of collateral causes creditors to remain in their preferred creditor position.Keywords: Justice; Absolute; Material Rights; Material Security; Privileges.